2022
DOI: 10.3390/genes13030541
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Reconstruction of Antarctic Fur Seals Supports the Krill Surplus Hypothesis

Abstract: Much debate surrounds the importance of top-down and bottom-up effects in the Southern Ocean, where the harvesting of over two million whales in the mid twentieth century is thought to have produced a massive surplus of Antarctic krill. This excess of krill may have allowed populations of other predators, such as seals and penguins, to increase, a top-down hypothesis known as the ‘krill surplus hypothesis’. However, a lack of pre-whaling population baselines has made it challenging to investigate historical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Additionally, N E /N C is influenced by the choice of genetic marker, so its interpretation relies on precise knowledge regarding the distribution of genetic variation across the genome [75]; its impact on N E is not fully understood. Therefore, an additional estimation of N E for leopard seals based on genome-wide data would be beneficial as has been demonstrated with Antarctic fur seals [76]. Despite this, our findings suggest that leopard seal visual surveys may undercount animals.…”
Section: Effective Population Size Vs Census Sizementioning
confidence: 73%
“…Additionally, N E /N C is influenced by the choice of genetic marker, so its interpretation relies on precise knowledge regarding the distribution of genetic variation across the genome [75]; its impact on N E is not fully understood. Therefore, an additional estimation of N E for leopard seals based on genome-wide data would be beneficial as has been demonstrated with Antarctic fur seals [76]. Despite this, our findings suggest that leopard seal visual surveys may undercount animals.…”
Section: Effective Population Size Vs Census Sizementioning
confidence: 73%
“…The extensive removal of baleen whales throughout the southwest Atlantic by whaling during the early to mid‐20th century substantially reduced competition for food among krill‐dependent seabirds and seals (Laws 1977, Hodgson & Johnston 1997, Surma et al 2014). The krill surplus appears to have allowed the recovery of the AFS subpopulation at South Georgia which reached equal to, or possibly twice, its pre‐sealing size at peak recovery (Foley & Lynch 2020, Hoffman et al 2022). Conversely, large increases in some Antarctic whale populations in recent decades (Branch 2011, Pallin et al 2018, Zerbini et al 2019) are likely escalating resource competition with other krill‐dependent predators (Ballance et al 2006, Trivelpiece et al 2011, Savoca et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, a comparative study of ice breeding seals reported very high DQA allelic diversity (39 alleles in 30 individuals) in the world’s most abundant pinniped, the crabeater seal, while diversity was intermediate in Weddell and Ross seals, and lowest in leopard seals 31 . Furthermore, although Antarctic fur seals experienced a strong demographic reduction due to historical sealing, the effective population size during the bottleneck likely remained in the hundreds 72 , 75 , 76 . By contrast, the pinniped with the lowest recorded MHC diversity, the northern elephant seal, was hunted down to just a few tens of individuals, which may have resulted in the loss of MHC alleles through genetic drift 27 , 70 .…”
Section: Discussionmentioning
confidence: 99%